Information Technology Investment and Bank Performance in Pakistan - Pham, Phat Tien; Hussain, Sarfraz; Quddus, Abdul; Nguyen Xuan, Thuan; Tran Ba, Tri (Tạp chí Khoa học HUFLIT, 2023)
This paper aims to estimate the effect of information technology investment on commercial banks' performance in Pakistan. The sample of 27 banks from 2007 to 2019 is collected from the State Bank of Pakistan, the World Bank website, and the bank's website. The fixed-effect model and the random-effect model are used to estimate the four regressions. The dependent variables of quantitative models encompass ROA, ROE, ROS, and EPS. The independent variables consist of the ratio of IT expense on the total asset, non-interest expense, and revenue. The control variables of the models are bank size, bank age, and inflation. For robustness check, we use the Generalized Method of Moments approach. The findings give that the significant impact of information technology investment on bank performance, namely the ratio of information technology budget on the expense, is favorable to bank performance. In contrast, the ratio of the information technology budget on revenue is negative. Furthermore, the significant relationship between performance variables and other variables is not consensus in different models.